The 'militant democracy' principle in modern democracies [ - Thiel, Markus , 1973- (Ashgat, 2009)
A collection that analyses key country approaches to Militant Democracy. Featuring contributions from some of the key people working in this area, it presents a stocktaking of the legal measures to protect the democracy against its enemies within. It examines the legal and political provisions to defend the democratic structure against attacks